Molecularly imprinted polymer-based electrochemical biosensors for medical diagnostics: Artificial intelligence perspective - Bilgin, Aleyna Esma; Aydin, Feyza; Kalkan, Mert Furkan; Cosgun, Ali Samet; Jampasa, Sakda; Ozer, Tugba (ELSEVIER SCI LTD, 2026)
Molecularly imprinted polymers (MIPs) have emerged as a significant advancement in the realm of electrochemical biosensors, primarily due to their advantages in rapid, enzyme-free, precise, and cost-effective pathogen detection. The functional properties of MIPs can be tailored through the careful selection of formulation components. This review aims to examine MIP-based technologies utilized for the identification of disease biomarkers, encompassing a range of targets such as bacteria, viruses, C-reactive protein, necrosis factor-alpha, and antibodies, including Immunoglobulin G (IgG) and Immunoglobulin M (IgM). Additionally, the discussion will focus on the materials employed, such as polypyrrole, poly(o-phenylenediamine), and poly(aminophenol), while assessing the selection of monomers, templates, crosslinking agents, and modifiers that can enhance the sensing performance of MIPs. Moreover, this review will highlight the applications of MIPs across diverse
Keywords: Molecularly imprinted polymer; Electrochemical Biosensors; Biomarkers; Nanomaterials; Artificial Intelligence; ULTRASENSITIVE DETECTION; VIRUS; SENSORS; FILMS; Engineering; Instruments & Instrumentation